Transformational Leadership and Positive Discipline Culture in Indonesian Public Primary Schools: A Predictive Association Study - Rani Setyawati; supandi supandi; Nurkolis Nurkolis (Research, Training and Philanthropy Institution Natural Aceh, 2026)
Despite growing policy emphasis on positive discipline in Indonesian schools, empirical evidence on leadership predictors of discipline culture remains limited. This study examines whether principals' transformational leadership is associated with positive discipline culture in Indonesian public primary schools. Using a quantitative ex post facto (correlational) survey design, data were collected from 130 teachers across 20 public primary schools using proportionate stratified random sampling to ensure school-level representation. Teachers completed validated Likert-scale questionnaires measuring transformational leadership (36 items; α = .975) and positive discipline culture (36 items; α = .975). Simple linear regression indicated that transformational leadership significantly predicted positive discipline culture (R² = .579; B = 0.718; p < .001), representing a large effect size (f² = 1.375). This study contributes district-level evidence positioning positive discipline culture as a proximal organizational outcome sensitive to transformational leadership behaviors. Implications for principal professional development, leadership coaching, and district-level supervision are discussed. The cross-sectional, self-report design limits causal inference and generalizability.